(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
Preventing illness and maintaining a healthy lifestyle requires actions that benefit one's health. Literacy has various potential benefits for one's health and well-being, and these benefits are manifest in health promotion behavior. The present study measures literacy levels among adults in selected rural communities in River State, Nigeria. A convenience sample of one hundred and eleven adults residing in the rural communities of Omoku, Ahoada, Ikwere, Omuma, and Tai local government areas participated in the study. The respondents, comprising males and females aged 40 to 65, completed a self-report measure of the adult literacy questionnaire. The result demonstrated that most participants scored low on the literacy scale (57.75%). Whereas 31.25% of the participants scored high on the LS. The finding has implications for developing adult literacy in rural communities in River State, Nigeria.